Analysis of the Effect of the Amount of Explosives on Ground Vibration Due to the Explosion in the Purnama Pit PT. Agincourt Resources North Sumatra Province - Junior, Prince Robert; Wardana, Novandri Kusuma; Prastowo, Rizqi (ReTII, 2023)
PT Agincourt Resources is a company engaged in gold mining. The mining location of PT Agincourt Resources is located in Aek Pining Village, Batangtoru District, South Tapanuli Regency, North Sumatra Province, the mining method used by this company is Open Pit (open pit). Ground vibration is one of the blasting effects that must be considered, especially when mining activities are near important buildings, so vibration measurements must be carried out every time a blast is carried out. This research is focused on the Purnama pit which is about 30 meters from the processing plant. This research was conducted by measuring the vibrations resulting from blasting using a Micromate measuring instrument. This measurement aims to determine the effect of the amount of explosives on ground vibration, to determine the prediction of blasting vibration using the PPV equation, and to determine the level of ground vibration according to SNI 7571:2010. The results showed that the greater the maximum amount of explosive charge per delay time, the resulting ground vibration intensity will increase. Based on the data obtained, namely the relationship between the Scaled Distance value and the actual PPV in the field using power regression analysis, the constant value K = 596.76 and n = -1.633. The comparison of actual and predicted ground vibrations obtained is quite accurate with an average prediction accuracy value of 77.80%.